Evaluation of Yield and Yield Related Traits of Grain Amaranth (Amaranthus spp.) Accessions in Garhwal Hills of Uttarakhand - Paliwal, Arunima; Kumar, Ajay; Kumar, Pankaj; Vasishth, Amol (International Journal of Economic Plants, 2022)
The field study was conducted during July to November 2017at Crop Improvement Block of College of Forestry, VCSG Uttarakhand University of Horticulture and Forestry, Ranichauri, Uttarakhand, India. The experiment was setin an augmented block design along with 4 check varieties Annapurna, PRA-2, PRA-3 and Durga. The check varieties were planted after every 05 germplasm accessions to evaluate the yield variation among different germplasm accessions of grain amaranth for crop improvement. Data on yield and other parameters were recorded as per the standard procedure and were analyzed by analysis of variance using statistical software to establish the significant variations. There was quite high variation among the germplasm accessions for plant growth, seed yield and yield contributing characters like 10 ml test weight, Inflorescence length, No. of finger plant-1, Finger length and seed yield. Seed yield of the germplasm accessions ranged from 0.94-25.00 g plant-1. Conditions for seed setting and filling of grains in grain amaranth were, in general, poor that resulted in low seed yields. The promising germplasm accession for higher seed yield plant-1 was found in accession IC037156 which was more than the best check Durga. So, IC037156 can be preferred for further crop improvement regarding promotion of the genotype